(untitled) (Indian Journal of Nematology, 2024)
Nematodes, parasitizing crop plants, are one of the key biotic stressors that cause substantial yield loss to the global food production system. According to a conservative estimate, PPNs cause an annual yield loss of 173 billion US dollars globally in diverse crops. Understanding the basis of nematode-host interaction along with functional genomic studies on plant parasitic nematodes has helped in designing molecular strategies for nematode management. Engineering resistance against plant parasitic nematodes by developing transgenic plants through transferring the R gene, or host-delivered dsRNA molecules targeting crucial nematode genes are seen as academic successes but have not translated into any product that can be cultivated because of the non-availability of permissions from the biosafety regulators of scientific bodies in the country. CRISPR/Cas9 gene editing technology will transform agriculture as newer varieties can be produced at a very fast pace with easy and cheap protocols. Nematode resistance can also be engineered in crop plants using this technology.